STUDI TENTANG FAKTOR-FAKTOR ATMOSFER LINGKUNGAN TERHADAP KETERIKATAN PELANGGAN PADA COWORKING SPACE DI YOGYAKARTA - Darusuprapta, Faizal; Dirgantara, I Made Bayu (Faculty of Economics and Business Diponegoro University, 2019)
Bussines competition among coworking space have been emerging along with therise of coworking space amount each year. Competition in the business world is one of thereasons companies compete with each other in innovating products, goods and servicesproduced. To maintain the remaining market and reach a higher share of the market firmsmust construct new and attractive marketing strategies. This study aims to study the effectof atmosphere on customer engagement in Sinergi Co-Work and Network SpaceYogyakarta. This research used 140 respondents as customer of Sinergi Co-Work andNetwork Space di Kota Yogyakarta. The sampling method used a non-probability samplingmethod with a purposive sampling technique. The Collecting data used quantitativemethod with questionnaire media that was analyzed afterwards by Structural EquationModeling (SEM). The findings show that social factor have positive and significant effecton customer satisfaction, public design factor have a positive effect but does not meet therequirements of significance to customer satisfaction, room design factor have a positiveand significant effect on customer satisfaction, the ambience factor have a positive andsignificant effect on customer satisfaction, customer satisfaction have a negative effect andsignificant effect on willingness to suggest, and customer satisfaction have a positive andsignificant effect on word of mouth.